Pengaruh Kompensasi, Keterlibatan Kerja, Hubungan Antar Karyawan Terhadap Retensi Karyawan pada Perumda Pasar Joyoboyo Kota Kediri - patrisia, anisa; Miftahul Munir; Anita Sumelvia (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2025)
The study aims to explain and prove the hypothesis regarding the influence 0f compensation, work involment, and inter-employee relations at perumda pasar joyoboyo, Kediri city. The method used in this study uses a quantitave method with a non-probability sampling technique with a saturated sample method with a population of 41 employees and a sample of 41 employees. The analysis techniques used in this study are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, T test (partial), F test (simultaneous), determinant coefficient test, (R2) wich are processed using SPSS. The research result show that compensation and job involment variables do not affect employee retention, while the variable of employee relationships affects employee retention, and simultaneously, the three variables affect employe retention.